Recruitment and Selection Process of Personnel of Central Pattana Company Khon Kaen Co., Ltd. - Thanawis (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2023)
Abstract The objectives of this research were to study the process of recruiting and selecting personnel and to analyze strengths, weaknesses, opportunities, and obstacles in recruiting and selecting personnel for the Human Capital Management Department, Central Pattana Khon Kaen Company Limited. It was qualitative research. I collected data from five informants and analyzed the data by using content analysis. The results of the research found that: 1. The recruitment and selection process has established criteria for consideration, namely applicant qualifications, suitability for position, skill, and attitude. 2. The strength of recruiting and selection is that there is a clear recruiting and selection process according to the system. The selection criteria for the interview must be appropriate and consistent with the position. 3. The weakness of recruiting and selection is that the interview location is not enough. The process for processing the application is delayed and takes a long time. 4. Recruitment and selection opportunities are based on corporate reputation and diverse recruiting channels and selection processes. 5. Obstacles to recruiting and selecting people are that the applicant's qualifications do not match the job title. Keyword: Process; Recruitment; Selection